Implementing Pancasila Values in Facing the COVID-19 Pandemic – A Study from the City of Cimahi - Arnie Fajar; Lili Halimah; Heni Heryani (JED (Jurnal Etika Demokrasi), 2023)
Pancasila as the basis and ideology of the state cannot be separated from community programs, because the values in it are the original characteristics of the Indonesian. These values teach how to think and act in overcoming various problems in the life of the nation and state. During the COVID-19 pandemic, it has caused a crisis for the Indonesian, especially for the economic sector. This study aimed to find out the embodiment of Pancasila values that grew and developed in people's lives in Cimahi City during the COVID-19 pandemic. The approach used was qualitative approach. There were 115 respondents who were interviewed in three sub-districts and sub-districts, namely 30 respondents in Cibeureum Subdistrict (South Cimahi Subdistrict), 20 respondents in Cimahi Subdistrict, and 20 respondents in Setiamanah Subdistrict (Cimahi Tengah Subdistrict), 25 respondents in Citereup Subdistrict, and 20 respondents in Cipageran Subdistrict (North Cimahi District). The results of the study show that the values of Pancasila as the basis and ideology of the Indonesian state, are the values that could strengthen community resilience in overcoming crises. The strength of these values was shown by their belief in God the Almighty and obedience to worship both horizontally and vertically, the belief that humans are born and created with the same dignity, respected each other without discrimination, promoting unity, togetherness and mutual cooperation, prioritizing deliberation based on the spirit of kinship in overcoming problems, being fair by maintaining an equality between obligations and rights. The people in Cimahi City were able to implement values in Pancasila as a way of thinking and acting to overcome the crisis of social life, as faced in the current pandemic situation.